Clinical Profile and Risk Factors of Syphilis Patients: The Threat of HIV Coinfection and Congenital Syphilis at the Tanjungpuri Sintang Community Health Center in 2025 - Dwiyana, Cynthia Oktora (STIKES ADVAITA MEDIKA TABANAN, 2026)
Syphilis cases are showing an upward trend globally, including in the working area of the Tanjungpuri Community Health Center, Sintang District. This infection not only affects individuals of productive age but also threatens the health of mothers and fetuses through the risk of co-infection and vertical transmission. This study aims to analyze the clinical profile and risk factors of syphilis patients in the working area of the Tanjungpuri Community Health Center, Sintang, in 2025. This quantitative descriptive study used a case study approach on 123 syphilis patients recorded at the Tanjungpuri Community Health Center during 2025. The data were analyzed univariately to see the frequency distribution of sociodemographic characteristics and clinical profiles. The majority of respondents were of productive age, unmarried (59.35%), had a high school education or equivalent (92.9%), and worked in the private sector (45.53%). Very low preventive behavior was found, with 99.19% of patients not using condoms. Clinically, 6 cases of STIs (4.88%) and 4 cases of HIV co-infection (3.35%) were found, all of which occurred in pregnant women. The recorded clinical effects include cases of abortion, intrauterine fetal death (IUFD), and one case of a newborn with congenital syphilis. Low health literacy and barrier protection behaviors are the main drivers of syphilis transmission. The finding of HIV co-infection in pregnant women and the emergence of congenital syphilis cases underscore the need to strengthen the Triple Elimination program through more aggressive early screening and treatment of sexual partners.